A flexible, multifunctional, active terahertz modulator with an ultra-low triggering threshold. Issue 30 (22nd June 2020) - Ma, He; Wang, Yu; Lu, Rong; Tan, Fangrui; Fu, Yulan; Wang, Guang; Wang, Dayong; Liu, Kai; Fan, Shoushan; Jiang, Kaili; Zhang, Xinping
Abstract : Flexible, multifunctional, active THz modulators with ultra-low triggering threshold were developed by aligned carbon nanotube thin films coated with VO2 . These active THz modulators find applications in THz communication and THz imaging. Abstract : Active terahertz (THz) modulators play an essential role in THz technology. Because of the excellent THz modulation properties bestowed by its intrinsic metal–insulator transition (MIT) at 68 °C, vanadium dioxide (VO2 ) is an appealing active THz modulator material. Current active THz modulator designs based on pure VO2 films or metasurfaces deposited on traditional semiconductor substrates are typically subject to high triggering thresholds and slow responses. Therefore, further development of VO2 -active THz modulators for superior performance requires new materials and device designs. In this paper, we develop a flexible active THz modulator based on an aligned carbon nanotube thin film coated with VO2 . THz wave modulation driven by the MIT of VO2 presents a giant modulation depth of up to 91% and broad bandwidth (>2.3 THz). Various stimuli can be utilized to trigger the THz modulator. The response time of the THz modulator is 27 ms, which can be further shortened by decreasing the device size. In addition, the light-triggering threshold is quite low (0.58 mW mm −2 ). Optical anisotropy enables polarization of the THz modulator. Since they combine superior modulation performance, responsive stimulus diversity, versatility, and flexibility, these active THz modulators find applications in THz communication, THz imaging, etc.